Clinical Placements: The Perspectives of UK Physiotherapy Students on How Prepared they were by their University for their First Clinical Placements: an example of one HEI - Thomson, Di; Boyle, Daniel; Legg, Christopher; Owen, Mathew; Newman, Melanie; Cole, Mary-Jane (International Journal of Practice-based Learning in Health and Social Care, 2016)
Background. Clinical placements are an integral component of physiotherapy education as they give physiotherapy students the opportunity to apply their academic knowledge and skills and at the same time universities aim to provide an education that responds to the demands of practice settings. Objective. This study aims to investigate the perceptions of second year physiotherapy students on a range of aspects regarding their university’s education as a preparation for their first clinical placement. Method. Second-year physiotherapy students were invited to participate in a survey before and after engaging in their first clinical placement. Domains covered by the survey were: knowledge and skills, professionalism, communication, inter-professional awareness, and stress, coping and support. Results. The findings revealed that although the students felt prepared with regard to their anatomy, physiology, manual handling and treatment strategies they felt unprepared in patient record keeping, clinical reasoning, goal setting and communicating with families and carers. Conclusion. Universities can do much to ease their students’ path into the clinical setting and create a seamless transition from academic life to the world of practice. Possible ways in which this could be achieved are discussed.